The clustering of the SDSS-IV extended baryon oscillation spectroscopic survey DR16 luminous red galaxy and emission-line galaxy samples: cosmic distance and structure growth measurements using multiple tracers in configuration space. Issue 3 (26th August 2020) - Wang, Yuting; Zhao, Gong-Bo; Zhao, Cheng; Philcox, Oliver H E; Alam, Shadab; Tamone, Amélie; de Mattia, Arnaud; Ross, Ashley J; Raichoor, Anand; Burtin, Etienne; Paviot, Romain; de la Torre, Sylvain; et al.
ABSTRACT: We perform a multitracer analysis using the complete Sloan Digital Sky Survey IV (SDSS-IV) extended Baryon Oscillation Spectroscopic Survey (eBOSS) DR16 luminous red galaxy (LRG) and the DR16 emission-line galaxy (ELG) samples in the configuration space, and successfully detect a cross-correlation between the two samples, and find the growth rate to be fσ 8 =0.342 ± 0.085 (∼25 per cent accuracy) from the cross-sample alone. We perform a joint measurement of the baryonic acoustic oscillation (BAO) and redshift space distortion (RSD) parameters at a single effective redshift of z eff = 0.77, using the autocorrelation and cross-correlation functions of the LRG and ELG samples, and find that the comoving angular diameter distance D M ( z eff )/ r d = 18.85 ± 0.38, the Hubble distance D H ( z eff )/ r d = 19.64 ± 0.57, and fσ 8 ( z eff ) = 0.432 ± 0.038, which is consistent with a ΛCDM model at $68{\ \rm per\ cent}$ CL. Compared to the single-tracer analysis on the LRG sample, the Figure of Merit of α ⊥, α ∥, and fσ 8 is improved by a factor of 1.11 in our multitracer analysis, and in particular, the statistical uncertainty of fσ 8 is reduced by $11.6{\ \rm per\ cent}$ .